Variasi posisional dan intensitas match physical demands pada pemain sepak bola internasional Indonesia: analisis komparatif berbasis global positioning system (GPS) - Alex Aldha Yudi; Roma Irawan; Eval Edmizal (Indonesian Institute for Counseling, Education and Theraphy, 2026)
This GPS-based comparative observational study analyzed match physical demands of Indonesian national soccer players in two international matches against Kyrgyzstan (n = 15 GPS records) and North Korea (n = 8 GPS records), held at Zhejiang Normal University Stadium, September 2023. Variables included total distance, distance per minute, maximum speed, high-speed running (HSR), sprint distance, number of HSR, number of sprints, explosive accelerations, decelerations, and speed zone distances. Descriptive statistics, Mann-Whitney U tests, rank-biserial effect sizes, and Spearman correlations were computed. Mean total distance ranged from 6,390–6,709 m, influenced by varied playing durations. Medium effect sizes (r = 0.317–0.358) were observed for HSR distance, sprint distance, and relative intensity (m/min) between matches. Spearman correlations confirmed strong internal consistency (HSR–Sprint: ρ = 0.886; nHSR–nSprint: ρ = 0.811). Full backs consistently obtained physical loads at a higher level than other players through both of the matches indicating a position-dependent demand profile. This data documented foundational normative GPS data for Indonesian international soccer and bear direct practical implications for individualized load monitoring, training periodization, and opponent-specific tactical preparation.